Impact of withdrawal of antiepileptic medication on the duration of focal onset seizures. (April 2019) - Hartl, E.; Seethaler, M.; Lauseker, M.; Rémi, J.; Vollmar, C.; Noachtar, S.
Highlights: analysis of 672 focal onset seizures with intracranial EEG recording. seizure rebound effect was observed after rapid AED withdrawal. seizures did not prolong after 2.5 half-lives (adjusted multivariate model). generalization rate of focal onset seizures did not change after 2.5 half-lives. Abstract: Purpose: To systematically evaluate the duration of focal onset seizures under medication withdrawal as a function of drug half-life. Methods: Adults with drug resistant focal epilepsy and invasive electroencephalographic (iEEG) recording between 01/2006 and 06/2016 (n = 128) were identified. Patients with multifocal or unknown epileptic foci were excluded, as well as subclinical seizures, isolated auras, or status epileptic. Antiepileptic drugs (AEDs) were withdrawn upon admission. The seizure duration was determined based on the invasive EEG data, and the latency since start of the monitoring was noted in hours. A negative binomial mixed model was used to compare the seizure durations before and after a cut-off, which was set at 2.5 half-lives of the individual anticonvulsive medication as this is thought to separate therapeutic and ineffective drug levels. Results: In total, 70 patients were included in the study and the duration of 672 seizures analyzed. On average, the patients were treated with 2.36 ± 0.78 AEDs. The individual cut-off of 2.5 half-lives was on average reached after 95.02 ± 80.18 h. The seizure frequency (321 vs. 351) and the rate of generalization (15.6% vs. 16.8%) was comparable before and after the individual cut-off point. The mean seizure duration was not statistically significantly prolonged after 2.5 half-lives by a factor of 1.168 for focal onset seizures (p = 0.090) and a factor of 1.091 for secondary generalized seizures (p = 0.545). Conclusions: Although AED withdrawal increases the likelihood for epileptic seizures, it did not prolong the seizure duration, nor did it increase the rate of secondary generalization in our study.